2023
DOI: 10.1002/ps.7490
|View full text |Cite
|
Sign up to set email alerts
|

Niche shifts and range expansions after invasions of two major pests: the Asian longhorned beetle and the citrus longhorned beetle

Abstract: Background: In recent years, the quarantine forestry pests the Asian longhorned beetle (ALB) Anoplophora glabripennis and the citrus longhorned beetle (CLB) Anoplophora chinensis have spread across the Northern Hemisphere, triggering concern about their potential distribution. However, little is known about the niche shifts of the pests during the invasion, making it difficult to assess their potential ranges. We thus employed two distinct approaches (i.e., ordination-based and reciprocal model-based) to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…Reliance on prophylactic applications of existing wide spectrum insecticides inevitably leads to further turns of the pesticide treadmill ( 8 ), exacerbating the risk of damage to non-target organisms and the natural environment ( 9 ). Ironically, anthropogenic declines of insect populations may affect natural enemies more than pests, thus worsening pest outbreaks ( 10 ).…”
Section: Lepidoptera As Insect Pestsmentioning
confidence: 99%
“…Reliance on prophylactic applications of existing wide spectrum insecticides inevitably leads to further turns of the pesticide treadmill ( 8 ), exacerbating the risk of damage to non-target organisms and the natural environment ( 9 ). Ironically, anthropogenic declines of insect populations may affect natural enemies more than pests, thus worsening pest outbreaks ( 10 ).…”
Section: Lepidoptera As Insect Pestsmentioning
confidence: 99%
“…21,25 The estimation of the niche shifts in invasive species provides an essential basis for tracking their invasion history and preventing further expansions. 24 Many studies have reported niche shifts in invasive pests, such as Hyphantria cunea, 26 Anoplophora glabripennis and A. chinensis, 27 and Popillia japonica. 28 Godefroid et al 29 compared the occupied climatic space of Chinese populations of D. valens and three native lineages in North America and found a close distance between the invasive population and native lineages in northeastern and western North America; however, recent evidence suggests that these results might be owing to the insufficient sampling in China.…”
Section: Introductionmentioning
confidence: 99%
“…The estimation of the niche shifts in invasive species provides an essential basis for tracking their invasion history and preventing further expansions 24 . Many studies have reported niche shifts in invasive pests, such as Hyphantria cunea , 26 Anoplophora glabripennis and A. chinensis , 27 and Popillia japonica 28 . Godefroid et al 29 .…”
Section: Introductionmentioning
confidence: 99%